Kewarisan Istimewa Gharawain Pasal 178 Ayat (2) Kompilasi Hukum Islam Dalam Isu Kesetaraan Perspektif Feminis Legal Teori - Ahmad Faza Bin Naja (Al Fuadiy Jurnal Hukum Keluarga Islam, 2023)
Article 173 of the Compilation of Islamic Law is an article regarding inheritance. This article contains the issue of "special" inheritance. What is meant by special here is a certain condition that causes this inheritance to be implemented. This inheritance case is known as Gharawain. That is the case of inheritance where there are only widow/widower heirs, with the mother and father. Where in this article the mother gets one-third and 1/3 of the remaining assets that have been distributed to the widow/widower. In fact, the gharawain concept has a 2:1 concept between men and women, it's just that the gharawain concept is not stated in the Al-Qur'an or Hadith, this legal product was produced from the ijtihad of the Prophet's friend, Umar bin Khattab. However, the concept of gharawain is included in an article in the Compilation of Islamic Law, so what is the concept of settling inheritance using gharawain and is article 178 paragraph (2) which adopts the concept of gharawain mandatory or is it only optional? The results of the discussion show that the solution to this concept is to change the mother's share from one third of the assets to the remaining third. So whether this concept should be implemented, it turns out it doesn't have to be implemented because of the differences in the context when this concept was created and the current context so feminists can still balance the differences in these parts.